The Regression Time of Bursa of Fabricius in ALPU Chickens - Riri Agusmanepi; Erina Erina; M Aman Yaman (Jurnal Medika Veterinaria, 2022)
This study aimed to determine the regression time of bursa Fabricius in ALPU chicken. In this research, 72 chickens of ALPU consisted of 36 males and 36 females, aged 1 week, 2 weeks,, until 18 weeks old were used. Each age group consisted of 2 male chickens and 2 female chickens. Bursa Fabricius of every age group was collected and weighed. The results showed that the weight of bursa Fabricius increased at 1 to 15 weeks old, and reached the maximum weight at 15 weeks of age. After reaching maximum weight, bursa Fabricius underwent regression that occurred at 16 to 18 weeks old. Bursa Fabricius’s weight increased in the starter phase at 1 to 6 weeks, grower at 7 to 12 weeks and will regress in the finisher phase at 13 to 18 weeks. The results of the average weight analysis of bursa Fabricius using t-test was observed by comparing the weight of bursa Fabricius ALPU chicken starter phase with grower phase and grower phase with finisher phase. The weight of bursa Fabricius of male ALPU on starter phase with grower phases was significanly difference (p0.05) whereas grower phase with finisher phase was not significantly difference (p 0,05). The weight of bursa Fabricius of female ALPU on starter phase with grower phases was significanly difference (p0.05), whereas grower phase with finisher phase was not significant (p 0,05). Therefore, it can be concluded that regression of bursa Fabricius occurred at the age of 16 to 18 weeks. The weight of bursa Fabricius in starter phase and grower phases are significantly difference, however there was no significantly difference was observed in finisher phase.